Effects of Implicit and Explicit Instruction on Learning Adjective Order - Shefali Elizabeth Mathew (ELT Worldwide: Journal of English Language Teaching, 2022)
This study tests the effect of implicit and explicit instruction in the learning of the order of adjectives for advanced second language learners of English. Ten participants were randomly divided into two groups of five each. The first group was shown grammatically correct and incorrect sentences, but were not given the details as to how the sentences were grammatically correct or incorrect. This was the group that received implicit instructions. The second group was given the same work sheet, but also received explicit instructions detailing the correct order of adjectives.  Following two trails rounds, both groups were given tests with 15 tasks to assess correct placement of adjectives in a sentence.  Results showed that those who received explicit instructions performed twice as well as those who received implicit instructions, making only five mistakes in total (33%), as opposed to ten mistakes made by those who had implicit instructions (66%). The most common mistakes were related to placement of the adjectives used for “opinion” and “physical quality”. The study supported the hypothesis that explicit instruction was more effective than implicit instruction in learning adjective order.